Perancangan Unit Instalasi Pengolahan Air Bersih Untuk Kebutuhan Kampus Universitas Panca Bhakti - Anggraini, Ika Muthya; Gunawan, Ivan Andri; Rahsia, Shandra Andina (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
Clean water is a fundamental necessity that plays a vital role in supporting various activities within higher education institutions, including Universitas Panca Bhakti (UPB). The availability of clean water that meets quality standards is essential to sustain academic activities, sanitation, laboratory work, and campus facility maintenance. However, the current condition shows that the existing water quality does not comply with the quality standards stipulated in the Indonesian Ministry of Health Regulation No. 2 of 2023. Therefore, a more reliable water treatment system is required. This study aims to design an adaptive and energy-efficient Clean Water Treatment Plant (CWTP) tailored to the characteristics of UPB"™s raw water sources. The methodology comprises three main stages: (1) analysis of raw water quality, (2) technical design of the treatment units, and (3) preparation of the Budget Plan (RAB). The raw water source is derived from rainwater runoff and campus catchment ponds, with an estimated annual potential supply of 88,313 m ³, which is sufficient to meet the campus"™s daily demand of 83.91 m ³. Laboratory tests indicated that the color and Total Coliform parameters exceeded the permitted limits, necessitating a treatment system that includes coagulation-flocculation, horizontal sedimentation, sand filtration, chlorine disinfection, and a clean water reservoir. The system is designed to operate at a capacity of 3.88 L/second, following the technical planning standards set in SNI 6774:2005, considering detention time, horizontal flow velocity, and filtration efficiency. The estimated construction cost for the treatment system is Rp85,900,000. This design is expected to serve as a sustainable and practical solution for clean water management on campus.